ANALISIS PENINGKATAN KESEJAHTERAAN MUSTAHIK MELALUI PENDAYAGUNAAN DANA ZAKAT PRODUKTIF DI LAZISNU JAWA TIMUR - Ach. Muhandis Mutiuddin; Ahmad Afif Amrullah; Uswatun Chasanah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
Abstract Productive zakat is the management of zakat by allocating zakat funds for productive programs aimed at improving the welfare of mustahik (zakat recipient) in a sustainable manner. This research aims to analyze the impact and effectiveness of utilizing productive zakat funds by lembaga Amil Zakat, Infaq and Shadaqah Nahdlatul Ulama (Lazisnu) East Java. The research method used is a qualitative approach with in-depth interviews, participant observation and document analysis. The sample for this research includes recipients of productive zakat benefits in Lazisnu, East Java who have participated in an economic empowerment program with the support of productive zakat funds. The research results show that the utilization of Lazisnu East Java's productive zakat funds has made a positive contribution in improving the welfare of mustahik. The economic empowerment program supported by productive zakat funds has provided business capital, business equipment and livestock housing. However, business activities and aid funds are still in the micro category, meaning that the increase in income has not had a significant impact on the welfare of mustahik. Keywords: Productive Zakat, Welfare, Mustahik, Lazisnu East Java Abstrak Zakat produktif adalah pengelolaan zakat dengan mengalokasikan dana zakat untuk program-program produktif yang bertujuan meningkatkan kesejahteraan mustahik (penerima zakat) secara berkelanjutan. Penelitian ini bertujuan untuk menganalisis dampak dan efektivitas pendayagunaan dana zakat produktif oleh Lembaga Amil Zakat, Infaq, dan Shaadqah Nahdlatul Ulama (Lazisnu) Jawa Timur. Metode penelitian yang digunakan adalah pendekatan kualitatif dengan wawancara mendalam, observasi partisipatif, dan analisis dokumen. Sampel penelitian ini mencakup penerima manfaat zakat produktif di Lazisnu Jawa Timur yang telah mengikuti program pemberdayaan ekonomi dengan dukungan dana zakat produktif. Hasil penelitian menunjukkan bahwa pendayagunaan dana zakat produktif Lazisnu Jawa Timur telah memberikan kontribusi positif dalam meningkatkan kesejahteraan mustahik. Program pemberdayaan ekonomi yang didukung oleh dana zakat produktif telah memberikan modal usaha, alat usaha dan rumah ternak. Namun kegiatan usaha dan dana bantuan masih kategori mikro membuat peningkatan penghasilan belum signifikan memberikan dampak pada kesjahteraan pada mustahik. Kata Kunci: Zakat Produktif, Kesejahteraan, Mustahik, Lazisnu Jawa Timur